Domains in the practice of the football learning: comparative study among football athletes of junior category in Portugal and Brazil - Koslowsky, M.; Ferreira da Conceicao Botelho, M. (Journal of Human Sport & Exercise, 2010)
This study aims to characterize the specific domains (SPD) and non-specific domains (NSD) of practice on the procedures of learning training in football, quantifying and identifying the experiences in order to find possible links between the estimates of accumulation of spent hours, relating them to the general aspects of practice. In this study, it was used a model of semi-structured interview. The sample (N=40), was composed of male subjects, athletes from junior category (u-20) from different populations - Portugal (pt=20) and Brazil (br=20), enabling comparative analysis of the results. After collecting the data, we analyzed the possible relationship between the profile of practice and the general aspects of training that each athlete analyzed. Regarding the discussion of the data, we made up comparisons of the results between the two clubs where the interviews were applied. The results are summarized having in mind the following aspects: (a) Portuguese Athletes (about 3000 hrs) have more experience in specific areas than Brazilian athletes (about 2600 hrs) up to 18 years old, (b) Brazilian Athletes (approx. 1600 hrs) have more experience in areas than non-specific athletes Portuguese (about 1000 hrs) up to 18 years old.